2009
DOI: 10.1016/j.mce.2009.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of bank vole pancreatic islet function by proinflammatory cytokines

Abstract: Please cite this article as: Blixt, M., Niklasson, B., Sandler, S., Suppression of bank vole pancreatic islet function by proinflammatory cytokines, Molecular and Cellular Endocrinology (2008), doi:10.1016/j.mce.2009 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…In comparison to human islets, the bank vole islets display a similar response in stimulation index and in insulin content with increasing glucose concentration in the culture medium (Eizirik et al 1992b). Interestingly, we recently found that bank vole islets responded to proinflammatory cytokines in vitro according to a pattern more resembling human islets than that seen in rodent islets (Blixt et al 2009). …”
Section: Discussionmentioning
confidence: 87%
“…In comparison to human islets, the bank vole islets display a similar response in stimulation index and in insulin content with increasing glucose concentration in the culture medium (Eizirik et al 1992b). Interestingly, we recently found that bank vole islets responded to proinflammatory cytokines in vitro according to a pattern more resembling human islets than that seen in rodent islets (Blixt et al 2009). …”
Section: Discussionmentioning
confidence: 87%
“…The second phase of pulsatile insulin secretion is related to the islet insulin content [ 19 ]. Hence, the insulin content in the medium of isolated islet is consisting of insulin secretion and amount or formation of insulin [ 20 , 21 ]. Therefore, present results demonstrated that low dose and high dose of eugenol administration were more potent on insulin content of pancreatic islets in hypo- and hyperglycemic conditions, and it can be suggested that these doses of eugenol have more impact on the second phase of insulin release via mobilizing of subsequent supply for producing new granules that contain insulin.…”
Section: Discussionmentioning
confidence: 99%
“…Post-transplantation apoptosis in human islets can be attributed by inflammatory factors. In the early stages of transplantation, human islet function is suppressed by pro-inflammatory cytokines [ 10 , 11 ], which can stimulate the c-JNK islet cell apoptosis pathway. Upon activation of the apoptosis pathway, human islet cells could consequently release more pro-inflammatory cytokines which could attract and activate leukocytes.…”
Section: Introductionmentioning
confidence: 99%